2017
DOI: 10.1002/app.44927
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and properties of poly(siloxane‐ether‐urethane)‐acrylic hybrid emulsions

Abstract: Poly(siloxane-ether-urethane)-acrylic (PU-AC) hybrid emulsions were prepared by introducing different hydroxyethoxypropyl-terminated polydimethylsiloxane (PDMS) content into the acrylic-terminated poly(ether-urethane) backbone and then in situ copolymerizing with methyl methacrylate and butyl acrylate via emulsion process. The effects of PDMS on the particle size and viscoelastic behavior of the hybrid emulsions were investigated. Meanwhile, the hydrogen bonding, mechanical and thermal mechanical properties, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…PS-WPU 1 without PDMS exhibits the highest storage modulus, and the storage modulus of the PS-WPU samples decreases with increasing PDMS content. The storage modulus is a measure of material stiffness [39][40][41], and the incorporation of PDMS into the soft segment of the WPU decreases the stiffness because of the high flexibility of the PDMS. Figure 5b displays the tan δ curves, which are directly related to the T g of the PS-WPU samples.…”
Section: Dma Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…PS-WPU 1 without PDMS exhibits the highest storage modulus, and the storage modulus of the PS-WPU samples decreases with increasing PDMS content. The storage modulus is a measure of material stiffness [39][40][41], and the incorporation of PDMS into the soft segment of the WPU decreases the stiffness because of the high flexibility of the PDMS. Figure 5b displays the tan δ curves, which are directly related to the T g of the PS-WPU samples.…”
Section: Dma Analysismentioning
confidence: 99%
“…When the films are immersed in water, the water fills the microcavities and they swell due to the interaction between the hydrophilic groups and water, resulting in the absorption of water. However, incorporating hydrophobic PDMS creates a hydrophobic barrier on the surface to prevent water absorption and reduce the interaction between hydrophilic groups and water [31,41,53,54]. Thus, it can be concluded that by incorporating hydrophobic PDMS into the soft segment of the PU chains, the water resistance of the PS-WPU films was enhanced.…”
Section: Surface Hydrophobicity and Water Resistancementioning
confidence: 99%
“…This is primarily caused by the Si–O–Si network structure [42,43]. During the film formation and crosslinking process, the presence of siloxane with low polarity can provide a thermodynamic driving force for its surface migration, decrease the surface energy, and make the surface hydrophobic [44], which leads to the observation shown in Figure 8. In the studies by Zhao et al [17] and Lei et al [29], the maximum water contact angle reached respectively 79.25° and 77.6°.…”
Section: Resultsmentioning
confidence: 99%
“…Low-polarity silicon-oxygen chains act as a barrier to prevent water from entering the silicone rubber. Silicon-oxygen chains can form a siloxane (Si-O-Si) network structure, which can shield hydrophilic groups and reduce the interaction between water and hydrophilic groups [38,39]. It can be found from the results that even with a relatively small amount of IDA, the hydrophobicity of the modified silicone rubber is still enhanced.…”
Section: Hydrophobicity Of Rtv Silicone Rubbermentioning
confidence: 99%